Effect of glycerol on densification of agricultural biomass - Emami, Shahram; Tabil, Lope G; Adapa, Phani (International Journal of Agricultural and Biological Engineering, 2015)
Experiments were conducted to verify the effect of adding glycerol for pelleting of selected agricultural crop residues, namely, wheat, barley, oat and canola straw. Single pelleting tests were conducted to study the effect of biomass type, hammer mill screen size, and crude glycerol content (co-product of biodiesel industry) on pellet quality (density and durability), ash content and gross heat of combustion. Four types of biomass were ground at three different hammer mill screen sizes of 6.4, 3.2 and 1.6 mm. Each biomass was mixed with three levels of glycerol of 2.5%, 5.0% and 7.5% by weight. Pellets were made at a pre-set load of 4 400 N (138.9 MPa) using single-pelleting unit attached to an Instron testing machine. Quality of pellets was determined by measuring pellet density, relaxed density, durability (measured by pellet drop test) and specific energy required to make a pellet. The gross heat of combustion and ash content of pellets were also determined and compared. The highest pellet density (988-1 133 kg/m3) and relaxed density (992-1 142 kg/m3) were obtained from biomass ground using a hammer mill screen size of 6.4 mm. A decrease in hammer mill screen size resulted in reduced durability. The highest durability of biomass obtained from hammer mill screen size of 6.4 mm ranged from 97%-100%. Addition of glycerol resulted in lower ash content in majority of pellets. The highest gross heat of combustion was observed in pellets made from wheat straw with 7.5% glycerol content (38.3 MJ/kg). Addition of glycerol resulted in lower pellet densities, lower ash content, no change in durability and higher gross heating values. DOI: 10.3965/j.ijabe.20150801.009 Citation: Emami S, Tabil L G, Adapa P. Effect of glycerol on densification of agricultural biomass. Int J Agric & Biol Eng, 2015; 8(1): 64－73.